2010
DOI: 10.1002/hep.23912
|View full text |Cite
|
Sign up to set email alerts
|

IL28B genotype is associated with differential expression of intrahepatic interferon-stimulated genes in patients with chronic hepatitis C

Abstract: Genetic variation in the IL28B region has been associated with sustained virological response (SVR) rates in chronic hepatitis C (CHC) patients treated with peginterferon-α and ribavirin. We hypothesized that IL28B polymorphism is associated with intrahepatic expression of interferon-stimulated genes (ISGs), known to influence treatment outcome. IL28B genotyping (rs12979860) and whole-genome RNA expression were performed using liver biopsies from 61 North American CHC patients. After correction for multiple te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
312
5
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 338 publications
(344 citation statements)
references
References 28 publications
25
312
5
1
Order By: Relevance
“…Previous studies suggested a low pretreatment hepatic miR-122 level may predict NR to IFN-based therapy (14,26) irrespective of serum or hepatic HCV RNA level (14,25). In this study, we consistently found no correlation between hepatic or serum miR-122 and serum HCV RNA level.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies suggested a low pretreatment hepatic miR-122 level may predict NR to IFN-based therapy (14,26) irrespective of serum or hepatic HCV RNA level (14,25). In this study, we consistently found no correlation between hepatic or serum miR-122 and serum HCV RNA level.…”
Section: Discussionsupporting
confidence: 59%
“…4,5 However, in the SNP expression database http://humangenome.duke.edu/software, no difference in peripheral blood mononuclear cell expression of IL28B on the basis of rs12979860 genotype has been noted. In addition, in two independent studies, 22,23 no differences in levels of intrahepatic IL28B gene expression on the basis of IL28B genotype were observed. Further studies are needed to elucidate the causal variants and the biological mechanisms underlying the association between IL28B genotype and HCV treatment response.…”
Section: Mechanisms Of Action Of Lambda Ifns and Role Of Il28bmentioning
confidence: 88%
“…Similarly, in RNA expression analyses from liver biopsies of 61 North American patients with chronic HCV, 164 transcripts were differentially expressed on the basis of rs12979860 genotype. 23 The IFN signaling pathway was the most enriched canonical pathway with differential expression (P < 10 À5 ), and most genes had higher expression in livers of individuals carrying the poor-response non-C/C genotypes.…”
Section: Mechanisms Of Action Of Lambda Ifns and Role Of Il28bmentioning
confidence: 96%
“…It has been shown that IFN-ks convey anti-HCV activity by inducing various ISGs [67]. Some investigators have been able to show that the expression of IL-28 in PBMCs was higher in subjects with the major IL-28B genotype than in those with the minor IL-28B genotype; however, the levels of IL-28 transcripts in liver tissue were comparable regardless of IL-28B genotype [68,69].…”
Section: Innate Immunity In Hcv Infection: Hla Alleles and Il-28b/ifn-k3mentioning
confidence: 99%